The role of epicardial adipose tissue in cardiac biology: classic concepts and emerging roles - Antonopoulos, A; Antoniades, C (Wiley, 2017)
Classic concepts about the role of epicardial adipose tissue (EpAT) in heart physiology include its role in cardiac metabolism, mechanical protection of coronaries, innervation and possibly cryoprotection of the heart too. Nevertheless, recent evidence has revealed that epicardial adipose tissue regulates multiple aspects of cardiac biology including myocardial redox state, intracellular Ca(2+) cycling, the electrophysiological and contractile properties of cardiomyocytes, cardiac fibrosis as well as coronary atherosclerosis progression. Moreover, it is now understood that the communication between EpAT and the heart is regulated by complex bidirectional pathways, since not only do adipokines regulate cardiac function, but also the heart affects EpAT biology via paracrine 'reverse' signalling. Such complex interactions as well as epicardial fat accumulation as a consequence of cardiac disease and epicardium to adipocyte differentiation should be taken into account by the clinical studies investigating EpAT as a risk marker and its potential as a therapeutic target against cardiovascular disease. Further in-depth exploration of the molecular mechanisms regulating the cross-talk between the heart and EpAT is expected to enhance our understanding regarding the role of the latter in cardiac physiology and relevant disease mechanisms.